2016
DOI: 10.1016/j.annepidem.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of name and age data provided about network members in a social network study of people who use drugs: implications for constructing sociometric networks

Abstract: Purpose Network analysis has become increasingly popular in epidemiologic research, but the accuracy of data key to constructing risk networks is largely unknown. Using network data from people who use drugs (PWUD), the study examined how accurately PWUD reported their network members’ (i.e., alters’) names and ages. Methods Data were collected from 2008 to 2010 from 503 PWUD residing in rural Appalachia. Network ties (n=897) involved recent (past 6 months) sex, drug co-usage, and/or social support. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…A probabilistic record linkage (PRL, also known as fuzzy-matching) algorithm was developed to link contacts (interviewee-reported full name, sex, and approximate age of contact) reported to be living in the study catchment area to their census record (name, age, and sex as reported for all household participants through the census) ( Méray, Reitsma, Ravelli & Bonsel, 2007 ). This method has previously been used in risk network studies in the United States, where most interviewees were found to report contact characteristics accurately ( Young et al, 2016 ). Because our interest was in inter-household, rather than intra-household support, only relationships between individuals living in different households were considered.…”
Section: Methodsmentioning
confidence: 99%
“…A probabilistic record linkage (PRL, also known as fuzzy-matching) algorithm was developed to link contacts (interviewee-reported full name, sex, and approximate age of contact) reported to be living in the study catchment area to their census record (name, age, and sex as reported for all household participants through the census) ( Méray, Reitsma, Ravelli & Bonsel, 2007 ). This method has previously been used in risk network studies in the United States, where most interviewees were found to report contact characteristics accurately ( Young et al, 2016 ). Because our interest was in inter-household, rather than intra-household support, only relationships between individuals living in different households were considered.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Brashears (2013) shows that people recall the structure of personal networks in ways that are biased towards common patterns in networks (e.g., over-reporting triadic closure); that is, we interpret what we observe about networks to make them more easily remembered. In other cases, salient aspects may be intelligible in the moment of observation (e.g., our network partners' names and ages), but have been shown to be recalled in more aggregate or fuzzy ways (Young et al 2016). Each of these suggest we encode general features, not specific details, of observed network features into our memories.…”
Section: Why Network Assortativity On Bundles Of Behaviors?mentioning
confidence: 99%
“…However, as with many aspects of network data collection, respondent burden rapidly increases: each additional name interpreter must be asked for each alter identified by the name generator. Therefore, when gathering network data, it is often thought to be even more important to optimize the efficiency and appropriateness of name interpreter items (Young et al, 2016), by avoiding the collection of irrelevant, redundant, costly, and/or time-consuming data (McCarty et al, 2007).…”
Section: Name Generators -Which Relationships?mentioning
confidence: 99%
“…Researchers are increasingly incorporating the types of evaluations described above into their data collection efforts (Phillips et al, 2017;An and Schramski 2015). But beyond simply describing patterns of data fidelity, researchers are increasingly demonstrating how any such imprecisions in relational data (e.g., mis-identifying characteristics of alters) can influence the interpretation of network patterns from the subsequent data (Young et al, 2016). Different strategies for handling partner disagreements on relationships can lead to altered estimates of a relationship's existence, duration, and content (adams and Moody, 2007;Phillips et al, 2017).…”
Section: Implications and Quality Assessmentmentioning
confidence: 99%